(3GdMQR GdefShH Edi CHj OLGfIs - (3GdNRQLj, CHh OLGfI, SeGc Hf NQTI, J(B11(3g`s ((3ESeGYjd Hf YQH TjQGRjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdSehGJ hGdCQV hLYd GdXdeGJ hGdfhQ Ke GdPjf caQhG HQHge jYOdhf gPG cJGH ef eMeO QShd Gddgs
(3BNQgG (B:s
(3dg eYbHGJ ef Hjf jOjg hef Ndag jMaXhfg ef CeQ Gddg aGddg NjQ MGaXG hgh CQMe GdQGMejf hdG Mhd hdG bhI EdG HGddg GdYdj GdYXjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 138s
(3GdEUGHI(B: (3HGH Gdcfi, hGdJQLeI (B371s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs